2008
DOI: 10.1128/jvi.00280-08
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the Active-Site Cysteine in the Ubiquitin-Specific Protease Contained in Large Tegument Protein pUL36 of Pseudorabies Virus Impairs Viral Replication In Vitro and Neuroinvasion In Vivo

Abstract: Herpesviruses specify a ubiquitin-specific protease activity located within their largest tegument protein.Although its biological role is still largely unclear, mutation within the active site abolished deubiquitinating (DUB) activity and decreased virus replication in vitro and in vivo. To further elucidate the role of DUB activity for herpesvirus replication, the conserved active-site cysteine at amino acid position 26 within pUL36 of Pseudorabies virus (PrV) (Suid herpesvirus 1), a neurotropic alphaherpesv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
69
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 51 publications
3
69
1
Order By: Relevance
“…4C) (35). The ΔDUB virus was incapable of transmission to the SCG despite productive replication in the iris, which is consistent with the prior observation that DUB activity is required for PRV spread from the AC to the brain, and demonstrates that this established CNS neuroinvasive defect is due to an upstream loss of PNS neuroinvasion (7,8). The K442R virus phenocopied the DUB mutant demonstrating that ubiquitination, in addition to deubiquitination, at K442 is critical for invasion of the PNS.…”
Section: Significancesupporting
confidence: 72%
See 1 more Smart Citation
“…4C) (35). The ΔDUB virus was incapable of transmission to the SCG despite productive replication in the iris, which is consistent with the prior observation that DUB activity is required for PRV spread from the AC to the brain, and demonstrates that this established CNS neuroinvasive defect is due to an upstream loss of PNS neuroinvasion (7,8). The K442R virus phenocopied the DUB mutant demonstrating that ubiquitination, in addition to deubiquitination, at K442 is critical for invasion of the PNS.…”
Section: Significancesupporting
confidence: 72%
“…Recent findings have provided insights into this complex phenotype, but the molecular mechanisms directing nervous system invasion are poorly understood (1)(2)(3)(4)(5). A critical effector of this process is a conserved herpesvirus deubiquitinase (DUB) (a cysteine protease that removes ubiquitin from target posttranslationally modified proteins) (6)(7)(8). The DUB is housed in the amino terminus of the pUL36 protein (protein encoded by the 36th open reading frame in the unique-long segment of the viral genome), amounting to less than 10% of the total mass of this large (>250 kDa) structural component of the virion (9).…”
mentioning
confidence: 99%
“…These studies indicated that an active USP was not essential for virus replication but that inactivity abrogated the infection process at some stage. Consistent with this, studies in pseudorabies virus (PRV) demonstrated that a virus with a substitution in the proposed catalytic cysteine of the PRV VP1-2 USP (C26S) resulted in a 20-to 30-fold reduction in virus yields in single-step growth curves, a reduction in plaque size (30%), and a delayed onset of pathogenic features after intranasal infection of mice (6). Moreover, in ultrastructural analysis of infection in culture, accumulations in nonenveloped cytoplasmic capsids were observed for the mutant virus, consistent with a defect in the known role of VP1-2 in virus assembly (6).…”
mentioning
confidence: 68%
“…Consistent with this, studies in pseudorabies virus (PRV) demonstrated that a virus with a substitution in the proposed catalytic cysteine of the PRV VP1-2 USP (C26S) resulted in a 20-to 30-fold reduction in virus yields in single-step growth curves, a reduction in plaque size (30%), and a delayed onset of pathogenic features after intranasal infection of mice (6). Moreover, in ultrastructural analysis of infection in culture, accumulations in nonenveloped cytoplasmic capsids were observed for the mutant virus, consistent with a defect in the known role of VP1-2 in virus assembly (6). In studies of a similar PRV mutant containing a C26A mutation, virus yields in culture were delayed and lower (10-to 20-fold), and a very significant defect was observed in animal models of neuroinvasion from peripheral tissues (27).…”
mentioning
confidence: 68%
“…These green fluorescent protein (GFP)-tagged HSV capsids (39) demonstrated kinesin-and dynein-mediated motility with a velocity and processivity similar to those seen in vivo (6). Furthermore, the in vitro motility was dependent (40) upon the large virally encoded tegument protein UL36p (VP1/2) that is known to recruit motors and to be required for motility and invasiveness in vivo (24)(25)(26)(41)(42)(43)(44)(45)(46). In this study, we modified our in vitro trafficking system to permit the study of HSV and PRV particle motility in bulk cytosol containing both naked and enveloped viral capsids.…”
mentioning
confidence: 99%